Leadership Strategies in Responding to the Decline of New Student Enrollment at Pesantren Tahfidz Satu Qur’an Jambi - Siti Annisa; Armida; Ahmad Fikri (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
This study aims to analyze the leadership strategies employed to address and respond to the decline in student enrollment. The research adopts a qualitative approach with a case study design, involving the pesantren’s leadership and asatidz as key informants. Data were collected through in-depth interviews, observations, and document analysis, and were subsequently analyzed interactively through data reduction, data display, and conclusion drawing. The findings indicate that leadership strategies are implemented in an integrated manner, encompassing the application of effective learning methods, enhancement of educational quality, assurance of competent human resources and teaching staff, active promotion through social media and school visits, as well as collaborative involvement of asatidz. The success of these strategies is supported not only by promotional activities but also by the quality of students’ learning experiences, which foster satisfaction, parental trust, and a positive reputation for the pesantren through word-of-mouth recommendations. The involvement of both leadership and asatidz reflects a participatory leadership model that synergizes quality management and institutional reputation, strategies aimed at addressing declining student enrollment and strengthening institutional attractiveness.